Excellent Electrocatalytic Hydrogen Evolution Reaction Performances of Partially Graphitized Activated-Carbon Nanobundles Derived from Biomass Human Hair Wastes - Sankar Sekar; Dae Hyun Sim; Sejoon Lee (Nanomaterials, 2022)
Carbonaceous materials play a vital role as an appropriate catalyst for electrocatalytic hydrogen production. Aiming at realizing the highly efficient hydrogen evolution reaction (HER), the partially graphitized activated-carbon nanobundles were synthesized as a high-performance HER electrocatalyst by using biomass human hair ashes through the high-temperature KOH activation at two different temperatures of 600 and 700 °C. Due to the partial graphitization, the 700 °C KOH-activated partially graphitized activated-carbon nanobundles exhibited higher electrical conductivity as well as higher textural porosity than those of the amorphous activated-carbon nanobundles that had been prepared by the KOH activation at 600 °C. As a consequence, the 700 °C-activated partially graphitized activated-carbon nanobundles showed the extraordinarily high HER activity with the very low overpotential (≈16 mV at 10 mA/cm2 in 0.5 M H2SO4) and the small Tafel slope (≈51 mV/dec). These results suggest that the human hair-derived partially graphitized activated-carbon nanobundles can be effectively utilized as a high-performance HER electrocatalyst in future hydrogen-energy technology.